Combination of Compensations and Multi-Parameter Coil for Efficiency Optimization of Inductive Power Transfer System - Guozhen Hu; Junkun Zhang; Junhua Wang; Zhijian Fang; Changsong Cai; Zhongzheng Lin (Energies, 2017)
A loosely coupled inductive power transfer (IPT) system for industrial track applications has been researched in this paper. The IPT converter using primary Inductor-Capacitor-Inductor (LCL) network and secondary parallel-compensations is analyzed combined coil design for optimal operating efficiency. Accurate mathematical analytical model and expressions of self-inductance and mutual inductance are proposed to achieve coil parameters. Furthermore, the optimization process is performed combined with the proposed resonant compensations and coil parameters. The results are evaluated and discussed using finite element analysis (FEA). Finally, an experimental prototype is constructed to verify the proposed approach and the experimental results show that the optimization can be better applied to industrial track distributed IPT system.